2006
DOI: 10.1002/jmv.20712
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral insulin resistance during treatment of chronic hepatitis C with peguilated interferon plus ribavirin

Abstract: No changes in the IR were observed after 6 months of treatment. Insulin resistance is related to the abdominal fat and anthropometrical parameters rather than to the antiviral treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
8
2
2
Order By: Relevance
“…In the bivariate analysis, IR was associated with age and anthropometric factors (BMI, waist circumference and weight categories); however, this association was not found in the multivariate analysis. Some studies also showed the association of age, waist circumference, and BMI to IR among HCV patients (9,10,11,13,18). IR was also associated with higher mean values of triglycerides and is most likely the result of the characteristics of the HCV replication cycle.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the bivariate analysis, IR was associated with age and anthropometric factors (BMI, waist circumference and weight categories); however, this association was not found in the multivariate analysis. Some studies also showed the association of age, waist circumference, and BMI to IR among HCV patients (9,10,11,13,18). IR was also associated with higher mean values of triglycerides and is most likely the result of the characteristics of the HCV replication cycle.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies showed that more than 50% of HCV infected individuals have IR (8,9). In Brazil, IR prevalence varies from 20 to 80% in HCV patients (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…All these considerations seem very interesting for the therapeutic approach regarding, for example, lifestyle changes (weight loss, abolition of alcohol consumption, cardio-vascular control) and metformin or peroxisome proliferator activated receptor -agonists assumption [11][12][13][14][15][16][17].…”
Section: Hcv and Diabetes Mellitusmentioning
confidence: 99%
“…Besides this, it is possible that liver siderosis and alterations in the levels of circulating adipocytokines might as well have a role in insulin sensitivity in CHC (39) . Nevertheless, Mello et al (35) failed to find an enhancement in insulin resistance, evaluated by HOMA (homeostatic model assessment), with the treatment of HCV.…”
Section: Introductionmentioning
confidence: 99%